PERAN BAHASA ARAB DALAM MEMAHAMI AL-QUR`ĀN DAN KORELASINYA DENGAN AJARAN MINARDI MURSYID DALAM MENAFSIRKAN AL-QUR`ĀN - Sofyan Siddik; Sabilul Muhtadin; Syafiq Riza Hasan (Al-Majaalis : Jurnal Dirasat Islamiyah, 2022)
Along with the proliferation of studies on the interpretation of the Qur’an in society, Muslims are becoming more and more religious. Although the Qur'an is in Arabic, this does not dampen their enthusiasm in exploring Islamic sciences. However, this enthusiasm is often not accompanied by the seriousness of Qur’anic interpreters in mastering the Arabic properly, both orally and in writing. As a result, confusion and irregularities in interpreting the Qur'an often occur. Unfortunately, this fatal error is often taken for granted by many scholars. So, instead of being enlightenment, it becomes a medium of misdirection. One of them is the study of the Qur'an interpretation under the guidance of Minardi Mursyid in Surakarta and surroundings. He has a lot of confusion in interpreting the Qur'an, so that finally the MUI (Indonesian Ulema Council) issued a fatwa regarding his error. The approach used by the researchers is qualitative by using the literature study method. The results of this study prove that there is a very strong correlation between the knowledge of Arabic and the science of the Qur'an interpretation, so that the scholars made one's ability to actively master the Arabic an absolute requirement for an interpreter of the Qur’an. Minardi Mursyid's inability to actively master the Arabic is the main cause of his deviation in interpreting the Qur'an. There is some evidence of his deviation in his writings and studies in society.